2021
DOI: 10.2147/jir.s308177
|View full text |Cite
|
Sign up to set email alerts
|

Pyroptosis: A New Regulating Mechanism in Cardiovascular Disease

Abstract: Pyroptosis is a kind of pro-inflammatory cell death. Compared with autophagy and apoptosis, pyroptosis has unique characteristics in morphology and mechanism. Specifically, pyroptosis is a kind of cell lysis mediated by the Gasdermin family, releases inflammatory cytokines IL-1β and IL-18. There are three different forms of mechanism, which are caspase-1-mediated, caspase-4/5/11-mediated and caspase-3-mediated. A large number of studies have proved that pyroptosis is closely related to cardiovascular disease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 124 publications
0
73
0
1
Order By: Relevance
“…An important characteristic of P2X7 is that the non-selective ion channels will open under the action of high extracellular ATP concentration, allowing macromolecules to pass through, and leading to the formation of NLRP3 inflammasome ( Yin et al, 2017 ; Zhou et al, 2021 ) NLRP3 is closely associated with MIRI ( Hu et al, 2019 ). NLRP3 can promote the release of inflammatory mediators from cardiomyocytes, such as IL-1β and IL-18, and induce pyroptosis ( Ji et al, 2021 ). Pyroptosis is frequently involved in the development of atherosclerotic heart disease, infectious diseases and nervous system-related diseases, that are characterized by the formation of inflammasome, the activation of gasdermin and caspase-1, and the release of pro-inflammatory factors.…”
Section: Introductionmentioning
confidence: 99%
“…An important characteristic of P2X7 is that the non-selective ion channels will open under the action of high extracellular ATP concentration, allowing macromolecules to pass through, and leading to the formation of NLRP3 inflammasome ( Yin et al, 2017 ; Zhou et al, 2021 ) NLRP3 is closely associated with MIRI ( Hu et al, 2019 ). NLRP3 can promote the release of inflammatory mediators from cardiomyocytes, such as IL-1β and IL-18, and induce pyroptosis ( Ji et al, 2021 ). Pyroptosis is frequently involved in the development of atherosclerotic heart disease, infectious diseases and nervous system-related diseases, that are characterized by the formation of inflammasome, the activation of gasdermin and caspase-1, and the release of pro-inflammatory factors.…”
Section: Introductionmentioning
confidence: 99%
“…The PI3K/Akt signaling pathway is an important pathway by which ginsenosides improve apoptosis. The activation of this pathway promotes angiogenesis, alleviates tissue hypoxia, suppresses cell damage, and improves MC apoptosis (Wang M. et al, 2021;Cao et al, 2021). Evidence showed that ginsenoside Rb1, Rb3, Rb2/Rb3 combination, Rd, Rg1, Rg2, Rg3, Rh1, Rh2, Rk3 activated the PI3K/Akt-mediated signaling pathway (Supplementary Table S1).…”
Section: Pi3k/akt-mediated Signaling Pathwaymentioning
confidence: 99%
“…Thirdly, evidence showed that pyroptosis occurred during the development of MIRI ( Xu XN. et al, 2021 ; Ji et al, 2021 ), and pro-apoptotic caspase-3 can cleave GSDME to induce pyroptosis ( Wang Y. et al, 2017 ). However, no study has confirmed the anti-pyroptosis effect of ginsenosides in improving MIRI.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…The former could trigger cell swelling, cell rupture, and promote the inflammation. 10 , 11 Besides, other important role of activated caspase-1 is to induce the ripeness and release of IL-18 and IL-1β, which have ability to aggregate inflammatory response. 12 Recently, pyroptosis has become a new topic in cancer research, many studies found that pyroptosis plays an essential regulator in tumor invasion, proliferation and metastasis.…”
Section: Introductionmentioning
confidence: 99%